A novel Internet‐based blended learning programme providing core competency in clinical research. Issue 2 (2nd December 2011) - Tsugihashi, Yukio; Kakudate, Naoki; Yokoyama, Yoko; Yamamoto, Yosuke; Mishina, Hiroki; Fukumori, Norio; Nakamura, Fumiaki; Takegami, Misa; Ohno, Shinya; Wakita, Takafumi; Watanabe, Kazuhiro; Yamaguchi, Takuhiro; et al.
Abstract: Rationale, aims and objectives We developed a novel Internet‐based blended learning programme that allows busy health care professionals to attain core competency in clinical research. This study details the educational strategies and learning outcomes of the programme. Method This study was conducted at Kyoto University and seven satellite campuses from September 2009 to March 2010. A total of 176 health care professionals who had never attempted to attain core competency in clinical research were enrolled. The participants were supplied with a novel programme comprising the following four strategies: online live lectures at seven satellite campuses, short examinations after each lecture, an Internet‐based feedback system and an end‐of‐course examination. We assessed the proportion of attendance at the lectures as the main outcome. In addition, we evaluated interaction via the feedback system and scores for end‐of‐course examination. Results Of the 176 participants, 134 (76%) reported working more than 40 hours per week. The mean proportion of attendance over all 23 lectures was 82%. A total of 156 (89%) participants attended more than 60% of all lectures and were eligible for the end‐of‐course examination. A total of the participants accessed the feedback system 3564 times and asked 284 questions. No statistically significant differences were noted in the end‐of‐course scores among medical doctors, pharmacists, registered nurses and other occupations. Conclusions We developed an Internet‐based blended learning programme providing core competency in clinical research. Most busy health care professionals completed the programme successfully. In addition, the participants could attain the core competency effectively, regardless of their occupation.